2020
DOI: 10.1016/j.cels.2020.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Gene Networks with Transcriptional Bursting Recapitulate Rare Transient Coordinated High Expression States in Cancer

Abstract: Highlights d Rare coordinated high expression states in cancer cells can drive therapy resistance d Gene networks with transcriptional bursting recapitulate these transcriptional states d Networks with low connectivity favorably give rise to these states d Parameters affecting transcriptional bursting are critical to produce these states

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 34 publications
2
74
0
Order By: Relevance
“…If so, the key to more durable therapy lies not in deeper inhibition of the core MAPK cascade, which might be toxic to non-transformed cells, but rather the identification of vulnerabilities specific to the persister state. This will benefit from better understanding of this state (Shaffer et al, 2017) and whether persister cells have recurrent features or vulnerabilities that can be targeted therapeutically (Schuh et al, 2020). These might include proteins downstream of multiple growth factor receptors (e.g., SHP2) (Chen et al, 2016), accumulation of DNA damage (Margue et al, 2019), or dependence on specific survival pathways (Coppé et al, 2019;Fallahi-Sichani et al, 2015;Hangauer et al, 2017).…”
Section: Physiological Configurationmentioning
confidence: 99%
“…If so, the key to more durable therapy lies not in deeper inhibition of the core MAPK cascade, which might be toxic to non-transformed cells, but rather the identification of vulnerabilities specific to the persister state. This will benefit from better understanding of this state (Shaffer et al, 2017) and whether persister cells have recurrent features or vulnerabilities that can be targeted therapeutically (Schuh et al, 2020). These might include proteins downstream of multiple growth factor receptors (e.g., SHP2) (Chen et al, 2016), accumulation of DNA damage (Margue et al, 2019), or dependence on specific survival pathways (Coppé et al, 2019;Fallahi-Sichani et al, 2015;Hangauer et al, 2017).…”
Section: Physiological Configurationmentioning
confidence: 99%
“…The interpretation of equation (14) is clear: in the deterministic limit, the rate of change in protein level is the burst frequency times burst size minus decay rate. Notably, both infinitesimally delayed and undelayed formulations lead to the same deterministic flow (14).…”
Section: Lyapunov Function Of the Deterministic Flowmentioning
confidence: 99%
“…with equality in (17) holding if x(t) = x is a fixed point of the deterministic flow (14). Thus, the distribution potential (16) is a Lyapunov function of (14), and has local minima (maxima) where the deterministic flow (14) has stable (unstable) fixed points. The dominant contribution towards the total probability mass (15) will thereby come from the neighbourhoods of points where the potential is minimal.…”
Section: Lyapunov Function Of the Deterministic Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in vitro studies have suggested that breast cancer cells are capable of freely transitioning between several phenotypic states including a putative cancer stem-cell phenotype 16 , suggesting that cell states are susceptible to nongenetic fluctuations. In vitro studies of melanoma have revealed that transcription bursting can give rise to a transient small population (~1 in 3,000) of pre-resistant cells based on concurrent high expression of several genes involved in resistance pathways 11,17 . Nongenetic heterogeneity has directly been shown to contribute to acquired drug resistance via inheritance of acquired characteristics in tracked single cells 18 .…”
Section: Introductionmentioning
confidence: 99%